Identifying the potential in the functional characteristics of the MRT Senayan Tod area - Taki, Herika Muhamad; Kuma, Julianus Pamungkas Payon; Radom, Wenseslaus Putra Arta (Akademisi dan Saintis Indonesia (ASASI), 2024)
The condition of Special Capital Region of Jakarta (DKI Jakarta), as one of the economic centers in Indonesia, has a very high level of population mobility, both from within and from other cities around it. The existence of the Jakarta Mass Rapid Transit (Jakarta MRT) aims to provide guidelines for creating a city environment that is oriented towards humans as users and/or the public interest, with an emphasis on aspects of functional quality, visual quality and environmental quality. With the MRT Senayan, we can implement a good Transit Oriented Development (TOD) area with structured land use selection. This writing aims to identify the potential for functional characteristics in the Senayan MRT TOD area. Senayan MRT region has medium potential according to the major line since it has complete pedestrian amenities, crossovers, and a bicycle track. Senayan MRT station has also become a significant Transit Oriented Development (TOD) region, connecting numerous major areas in Jakarta, including Senayan, Gelora Bung Karno, Blok M, and the central city. Transit Oriented Development zones can help to alleviate some of the city's or area's problems when implemented correctly.